Complex and adaptive dynamical systems a primer - Gros, Claudius; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
We are living in an ever more complex world, an epoch where human actions can accordingly acquire far-reaching potentialities. Complex and adaptive dynamical systems are ubiquitous in the world surrounding us and require us to adapt to new realities and the way of dealing with them. This primer has been developed with the aim of conveying a wide range of commons-sense knowledge in the field of quantitative complex system science at an introductory level, providing an entry point to this both fascinating and vitally important subject. The approach is modular and phenomenology driven. Examples of emerging phenomena of generic importance treated in this book are: The small world phenomenon in social and scale-free networks. Phase transitions and self-organized criticality in adaptive systems. Life at the edge of chaos and coevolutionary avalanches resulting from the unfolding of all living. The concept of living dynamical systems and emotional diffusive control within cognitive system theory. Technical course prerequisites are a basic knowledge of ordinary and partial differential equations and of statistics. Each chapter comes with exercises and suggestions for further reading - solutions to the exercises are also provided. This second edition adds a new chapter on quantifiying/measuring complexity in given systems, together with an introduction to information theory, has an expanded exercises and solutions section, and contains both revised and additional subsections.
About this book -- Graph Theory and Small-World Networks -- Chaos, Bifurcations and Diffusion -- Random Boolean Networks -- Cellular Automata and Self-Organized Criticality -- Statistical Modeling of Darwinian Evolution -- Synchronization Phenomena -- Elements of Cognitive System Theory -- Solutions -- Index.
Electronic reproduction.
Keywords: Differentiable dynamical systems; Adaptive control systems; Electronic books